APLICAÇÃO DO MAPEAMENTO DE FLUXO DE VALOR PARA REDUÇÃO DOS DESPERDÍCIOS DA PRODUÇÃO - Amaral, Tatiana; Araújo, Flávio (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Value Stream Mapping (MFV) is a tool that helps identify quality control failures and make planning a more efficient tool. In this sense, the objective of this work is the application of Value Stream Mapping (MFV) to minimize the waste of movement and transportation of an industry of soil-cement in Goiânia. For this purpose, production areas, equipment positions, inputs and finished products were determined; analyzes of the movements and the distances traveled by the employees during the production were accounted; and, the waste in the production were evaluated aiming the optimization of the times and movements. Were developed the MFV present and future to minimize production waste. These measures resulted in the reduction of the distances of employees and in the reduction of takt time.